2012
DOI: 10.1097/rli.0b013e318258502b
|View full text |Cite
|
Sign up to set email alerts
|

The Osmolality of Nonionic, Iodinated Contrast Agents as an Important Factor for Renal Safety

Abstract: The present results clearly show that prolonged iodine retention and the enhanced expression of kidney injury markers are caused mainly by the explicitly higher urine viscosity induced by iodixanol. We conclude that the osmolality of low-osmolar CAs such as iopromide induces a positive diuretic effect that is responsible for rapid iodine clearance and prevents increased expression of acute injury markers in the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Thus, urine viscosity was found higher in rats and dogs following IOCM than LOCM [19,20,26,42]; this was also corroborated in a small series of well hydrated patients [20]. Studies in rats and minipigs showed that the higher urine viscosity leads to a longer renal retention of IOCM than LOCM [32,35,41,43], which is accompanied by higher levels of injury markers [32,41]. Also, intrarenal oxygenation was much more compromised following IOCM than LOCM as monitored by invasive probes and blood oxygenation leveldependent (BOLD) magnetic resonance [20,32,33,35].…”
Section: Issn: 2380-0585mentioning
confidence: 68%
See 1 more Smart Citation
“…Thus, urine viscosity was found higher in rats and dogs following IOCM than LOCM [19,20,26,42]; this was also corroborated in a small series of well hydrated patients [20]. Studies in rats and minipigs showed that the higher urine viscosity leads to a longer renal retention of IOCM than LOCM [32,35,41,43], which is accompanied by higher levels of injury markers [32,41]. Also, intrarenal oxygenation was much more compromised following IOCM than LOCM as monitored by invasive probes and blood oxygenation leveldependent (BOLD) magnetic resonance [20,32,33,35].…”
Section: Issn: 2380-0585mentioning
confidence: 68%
“…Here, the difference in CM osmolalities plays a major role (290 versus 796 mosmol/kg H 2 O) [29,32,41]. Non-reabsorbable CM diminish the osmotic gradient that drives tubular water resorption, thereby inducing osmodiuresis.…”
Section: Issn: 2380-0585mentioning
confidence: 99%
“…However, a key difference between IOCM (iodixanol) and LOCM (iohexol) is the viscosity, with iodixanol being much more viscous than LOCM. This viscosity has been suggested to be a potential contributing factor in AKI seen in patients who receive iodixanol [27] and could negate any benefit that might derive from being iso-osmolar.…”
Section: Discussionmentioning
confidence: 94%
“…Its high osmolarity as well as a high viscosity can lead to poor patient tolerance. Dimeric iodine-based CA show an increase in retention in the kidneys [35] and can cause renal injury [36]. When comparing low-osmolarity CA with ones isotonic to blood plasma, a metastudy found a just-significant difference in contrast-induced nephropathy incidence [37].…”
Section: Contrast In X-raymentioning
confidence: 99%